Legal Protection for Underage Workers in Indonesia: Perlindungan Hukum bagi Pekerja di Bawah Umur di Indonesia - Muis, Lidya Shery; Putri , Auriel Nauvalia (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Child labor remains a persistent social and legal issue in Indonesia, challenging the state’s responsibility to protect children’s rights. Specific Background: Despite the existence of the Child Protection Act, many underage workers continue to experience exploitation without adequate legal enforcement. Knowledge Gap: Previous studies have focused on descriptive analyses of legal norms without assessing the practical application and effectiveness of protection mechanisms. Aim: This study aims to examine the legal framework and its implementation regarding the protection of underage workers in Indonesia. Results: The findings reveal that while Indonesia has a comprehensive legal basis, the enforcement is still weak due to limited supervision and social awareness. Novelty: The study provides a new interpretation of normative legal principles by emphasizing the synergy between legal regulations and social practices. Implications: The results highlight the need for stronger policy coordination and legal reinforcement to ensure that child protection laws are not only formal but also effectively implemented at all levels. Highlights:• The study identifies gaps in Indonesia’s legal protection for underage workers.• Enforcement weaknesses hinder effective child protection implementation.• Strengthening legal coordination is essential for policy improvement. Keywords: Child Labor, Legal Protection, Normative Law, Child Rights, Indonesia